The Impact of Climate Change on Tomato Water Footprint under Irrigation with Saline Water in a Kairouan Irrigated Area (Tunisia Center) - Khawla Khaskhoussy; Besma Zarai; Marwa Zouari; Zouhair Nasr; Mohamed Hachicha (Horticulturae)
The concept of the water footprint (WF) has not adequately explored the combined effects of climate change and salinity. For this aim, the effects of future climate conditions on tomato WF irrigated with moderately saline water (EC = 2.9 dS m−1) were examined, considering an expected increase in salinity reaching 5.9 dS m−1 by 2050. Reference evapotranspiration (ETo), effective rainfall (ER), tomato crop evapotranspiration (ETc), leaching requirement (LR), net irrigation requirement (NIR), and tomato yield were estimated using CropWat and AquaCrop models. The blue (WFBlue), green (WFGreen), gray (WFGray), and total WF (TWF) were calculated. Results showed that ETo, ETc, and ER are expected to increase, while tomato yields will show a slight decrease. NIR is expected to increase depending on climate change scenarios and the increasing salinity of water irrigation. Calculated WF components showed significant increases, which consequently led to an increase in WFT exceeding the Tunisian national and regional levels by 15% and 18% between 2023 and 2050 under two scenarios, RCP4.5 and RCP8.5. The results highlighted the importance of WF for developing adaptation strategies to manage limited water resources, while advanced research on a large scale based on smart assessment tools is required to find best practices for water use reduction.